Current Sensors Offset Fault Online Estimation in Permanent Magnet Synchronous Generator (PMSG) Drives for Offshore Wind Turbines - Xiaogang Ding; Yixuan Zhang; Zongbin Ye (IEEE Access, 2021)
Offshore wind power generation system’s reliability is always a challenging task. To solve the current sensor offset fault problem in the electric powertrain for the offshore wind power generation system, in this paper, a current-detection based sensor offset fault diagnosis method is proposed. The proposed method adopts four fixed measuring points for the estimation of the offset values, which does not require any modifications to the traditional PWM generating strategy. Therefore, the total harmonic distortion (THD) of the drive is not increased by using the proposed offset fault estimation method. The offset fault parameters of the powertrain system are obtained by analyzing the detected current sensors in the aforementioned four sampling points directly. No complex observers nor filters are needed for the signal processing, resulting in computational burden reduction. Experimental results on a 1 kW PMSG system demonstrated the effectiveness of the proposed strategy, which show that the current sensor offset faults can be estimated accurately, and the adverse effects can be eliminated.